Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

The Fourth Global Coral Bleaching Event: Where do we go from here? - James Davis Reimer; Raquel S. Peixoto; Sarah W. Davies; Nikki Traylor-Knowles; Morgan L. Short; Rafael A. Cabral-Tena; John A. Burt; Igor Pessoa; Anastazia T. Banaszak; R. Scott Winters; Tom Moore; Verena Schoepf; et al. (Coral Reefs, 2024)

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Lipoid liver disease in Hippocampus erectus Perry with Vibrio fortis ‐induced dermatitis and enteritis - Drayke Evans; Zachary Millar; Danielle Harding; Phuc H. Pham; Véronique LePage; John S. Lumsden (Journal of Fish Diseases, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Relationships between Pacific salmon and aquatic and terrestrial ecosystems: implications for ecosystem‐based management - Jessica C. Walsh; Jane E. Pendray; Sean C. Godwin; Kyle A. Artelle; Holly K. Kindsvater; Rachel D. Field; Jennifer N. Harding; Noel R. Swain; John D. Reynolds (Ecology, 2020)
Pacific salmon influence temperate terrestrial and freshwater ecosystems through the dispersal of marine‐derived nutrients and ecosystem engineering of stream beds when spawning. They also support large fisheries, particularly along the west coast of North America. We provide a comprehensive synthesis of relationships between the densities of Pacific salmon and terrestrial and aquatic ecosystems, summarize the direction, shape, and magnitude of these relationships, and identify possible ecosystem‐based management indicators and benchmarks. We found 31 studies that provided 172 relationships between salmon density (or salmon abundance) and species abundance, species diversity, food provisioning, individual growth, concentration of marine‐derived isotopes, nutrient enhancement, phenology, and several other ecological responses. The most common published relationship was between salmon density and marine‐derived isotopes (40%), whereas very few relationships quantified ecosystem‐level responses (5%). Only 13% of all relationships tended to reach an asymptote (i.e., a saturating response) as salmon densities increased. The number of salmon killed by bears and the change in biomass of different stream invertebrate taxa between spawning and nonspawning seasons were relationships that usually reached saturation. Approximately 46% of all relationships were best described with linear or curved nonasymptotic models, indicating a lack of saturation. In contrast, 41% of data sets showed no relationship with salmon density or abundance, including many of the relationships with stream invertebrate and biofilm biomass density, marine‐derived isotope concentrations, or vegetation density. Bears required the highest densities of salmon to reach their maximum observed food consumption (i.e., 9.2 kg/m 2 to reach the 90% threshold of the relationship’s asymptote), followed by freshwater fish abundance (90% threshold = 7.3 kg/m 2 of salmon). Although the effects of salmon density on ecosystems are highly varied, it appears that several of these relationships, such as bear food consumption, could be used to develop indicators and benchmarks for ecosystem‐based fisheries management.

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Development and evaluation of a porcine in vitro colon organ culture technique - Matheus O. Costa; John C. S. Harding; Janet E. Hill (In Vitro Cellular & Developmental Biology - Animal, 2016)

Early ocean distribution of juvenile Chinook salmon in an upwelling ecosystem - Jason L. Hassrick; Mark J. Henderson; David D. Huff; William J. Sydeman; Megan C. Sabal; Jeffrey A. Harding; Arnold J. Ammann; Eric D. Crandall; Eric P. Bjorkstedt; John Carlos Garza; Sean A. Hayes (Fisheries Oceanography, 2016)
Extreme variability in abundance of California salmon populations is often ascribed to ocean conditions, yet relatively little is known about their marine life history. To investigate which ocean conditions influence their distribution and abundance, we surveyed juvenile Chinook salmon ( Oncorhynchus tshawytscha ) within the California Current (central California [37°30′N) to Newport, Oregon (44°00′N]) for a 2‐week period over three summers (2010–2012). At each station, we measured chlorophyll‐ a as an indicator of primary productivity, acoustic‐based metrics of zooplankton density as an indicator of potential prey availability and physical characteristics such as bottom depth, temperature and salinity. We also measured fork lengths and collected genetic samples from each salmon that was caught. Genetic stock identification revealed that the majority of juvenile salmon were from the Central Valley and the Klamath Basin (91–98%). We constructed generalized logistic‐linear negative binomial hurdle models and chose the best model(s) using Akaike's Information Criterion ( AIC ) to determine which covariates influenced the salmon presence and, at locations where salmon were present, determined the variables that influenced their abundance. The probability of salmon presence was highest in shallower waters with a high chlorophyll‐ a concentration and close to an individual's natal river. Catch abundance was primarily influenced by year, mean fork length and proximity to natal rivers. At the scale of sampling stations, presence and abundance were not related to acoustic indices of zooplankton density. In the weeks to months after ocean entry, California's juvenile Chinook salmon population appears to be primarily constrained to coastal waters near natal river outlets.

Early Cretaceous palynostratigraphy of the Abu Tunis 1x borehole, northern Western Desert, Egypt, with emphasis on the possible palaeoclimatic effect upon the range of Dicheiropollis etruscus in North Africa - Amr S. Deaf; Ian C. Harding; John E.A. Marshall (Palynology, 2016)

Initial evaluations of a Gulf of Mexico/Caribbean ocean forecast system in the context of the Deepwater Horizon disaster - Edward D. Zaron; Patrick J. Fitzpatrick; Scott L. Cross; John M. Harding; Frank L. Bub; Jerry D. Wiggert; Dong S. Ko; Yee Lau; Katharine Woodard; Christopher N. K. Mooers (Frontiers of Earth Science, 2015)

Capital and income breeding: the role of food supply - Philip A. Stephens; Alasdair I. Houston; Karin C. Harding; Ian L. Boyd; John M. McNamara (Ecology, 2014)
An aspect of life history that has seen increasing attention in recent years is that of strategies for financing the costs of offspring production. These strategies are often described by a continuum ranging from capital breeding, in which costs are met purely from endogenous reserves, to income breeding, in which costs are met purely from concurrent intake. A variety of factors that might drive strategies toward a given point on the capital–income continuum has been reviewed, and assessed using analytical models. However, aspects of food supply, including seasonality and unpredictability, have often been cited as important drivers of capital and income breeding, but are difficult to assess using analytical models. Consequently, we used dynamic programming to assess the role of the food supply in shaping offspring provisioning strategies. Our model is parameterized for a pinniped (one taxon remarkable for the range of offspring‐provisioning strategies that it illustrates). We show that increased food availability, increased seasonality, and, to a lesser extent, increased unpredictability can all favor the emergence of capital breeding. In terms of the conversion of energy into offspring growth, the shorter periods of care associated with capital breeding are considerably more energetically efficient than income breeding, because shorter periods of care are associated with a higher ratio of energy put into offspring growth to energy spent on parent and offspring maintenance metabolism. Moreover, no clear costs are currently associated with capital accumulation in pinnipeds. This contrasts with general assumptions about endotherms, which suggest that income breeding will usually be preferred. Our model emphasizes the role of seasonally high abundances of food in enabling mothers to pursue an energetically efficient capital‐breeding strategy. We discuss the importance of offspring development for dictating strategies for financing offspring production.

Cretaceous (Albian–?early Santonian) palynology and stratigraphy of the Abu Tunis 1x borehole, northern Western Desert, Egypt - Amr S. Deaf; Ian C. Harding; John E. A. Marshall (Palynology, 2014)

The brain renin–angiotensin system: a diversity of functions and implications for CNS diseases - John W. Wright; Joseph W. Harding (Pflügers Archiv - European Journal of Physiology, 2013)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Recent Advances in Multichannel Seismic Imaging for Academic Research in Deep Oceanic Environments - Juan Pablo Canales; Hélène Carton; John Mutter; Alistair Harding; Suzanne Carbotte; Mladen Nedimović (Oceanography, 2012)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

Measurement error and estimates of population extinction risk - John M. McNamara; Karin C. Harding (Ecology Letters, 2004)
It is common to estimate the extinction probability for a vulnerable population using methods that are based on the mean and variance of the long‐term population growth rate. The numerical values of these two parameters are estimated from time series of population censuses. However, the proportion of a population that is registered at each census is typically not constant but will vary among years because of stochastic factors such as weather conditions at the time of sampling. Here, we analyse how such sampling errors influence estimates of extinction risk and find sampling errors to produce two opposite effects. Measurement errors lead to an exaggerated overall variance, but also introduce negative autocorrelations in the time series (which means that estimates of annual growth rates tend to alternate in size). If time series data are treated properly these two effects exactly counter balance. We advocate routinely incorporating a measure of among year correlations in estimating population extinction risk.

Estimating domain orientation of two human antibody IgG4 chimeras by crystallohydrodynamics - Emma Longman; Katja Kreusel; Saul B. Tendler; Immo Fiebrig; Kevin King; John Adair; Paul O'Shea; Alvaro Ortega; Jose Garcia de la Torre; Stephen E. Harding (European Biophysics Journal, 2003)

Common 5′ β-globin RFLP haplotypes harbour a surprising level of ancestral sequence mosaicism - Matthew T. Webster; John B. Clegg; Rosalind M. Harding (Human Genetics, 2003)

Overview of Operational Ocean Forecasting in the U.S. Navy: Past, Present & Future - William Burnett; John Harding; George Heburn (Oceanography, 2002)

The Scientific Foundations of Habitat Conservation Plans: a Quantitative Assessment - Elaine K. Harding; Elizabeth E. Crone; Bret D. Elderd; Jonathan M. Hoekstra; Alexa J. McKerrow; John D. Perrine; Jim Regetz; Leslie J. Rissler; Amanda G. Stanley; Eric L. Walters; Nceas Habitat Conservation Plan Working Group (Conservation Biology, 2001)
The number of habitat conservation plans ( HCP) has risen dramatically since the first plan was written over 18 years ago. Until recently, no studies have quantitatively investigated the scientific foundations underlying these documents. As part of a larger study of HCPs, we examined 43 plans primarily to assess the availability and use of scientific data and secondarily to determine the extent of involvement by, and influence of, independent scientists within the process. Specifically, our analysis focused on five key steps taken when an HCP is developed: assessing status of a species, determining take, predicting the project effects, mitigating for those effects, and monitoring of take and mitigation. In general, we found that the preparers of HCPs utilized existing scientific information fairly well, with 60% of plans not missing any available information described by our study as “starkly necessary.” The most common types of underutilized available data included those describing the influence of stochastic processes and habitat quality or quantity on species persistence. For many species, however, data on biology or status simply did not exist, as demonstrated by the fact that we could locate quantitative population estimates for only 10% of the species. Furthermore, for 42% of the species examined we had insufficient data and analysis to determine clearly how predicted take might affect the population. In many cases, mitigation measures proposed to offset take frequently addressed the most important local threats to the species with moderately reliable strategies. Species with monitoring programs rated as sufficient had plans that proposed to collect a greater amount of “quantitative” data than did those programs rated insufficient. Finally, when species “experts” were consulted, plan quality was generally higher. Overall, available scientific information in a majority of categories was fairly well utilized, but for many species additional studies and more in‐depth analyses were required to provide adequate support for issuance of an incidental take permit.

The relationship of BRMS1 and RhoGDI2 gene expression to metastatic potential in lineage related human bladder cancer cell lines - M. Jabed Seraj; Michael A. Harding; John J. Gildea; Danny R. Welch; Dan Theodorescu (Clinical & Experimental Metastasis, 2000)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

The effects of kainic acid lesions on dopaminergic responses to haloperidol and clozapine - M. E. Bardgett; Sheryl L. Salaris; Jamie L. Jackson; John Harding; John G. Csernansky (Psychopharmacology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

The ELLIPS suite of macromolecular conformation algorithms - S. E. Harding; John C. Horton; H. Cölfen (European Biophysics Journal, 1997)